Antiviral treatment options for covid-19 by reduction of viral load and viral shedding - Atif Amin, Baig; Chandrika, Murugaiah; Constance, Liew Sat Lin (2020)
The coronavirus disease 2019 (COVID-19) virus is a public health emergency of international concern, without known effective pharmaceutical treatment so far. It is difficult to treat infected patients who are experiencing acute respiratory failure, liver or cardiac injury, gastroenteritis and many other complications without any drug recommendation. Reducing the viral load is the most important key for Covid-19 treatment, where complication due to infection is highly correlated with the number of viral particles present in the lung and other organs of the patient. Most antivirals are effective against a wide range of viruses, where they inhibit viral development. Some of the possible antiviral treatment options for COVID-19 could be discovered from flu viral treatment that had led to quick respiratory illness recovery through reduction of viral load and viral shedding.